STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN FIZZYFUN MELALUI MEDIA SOSIAL - Setiawan, Levina; Sufiyati (Jurnal Serina Abdimas, 2024)
In the face of intense competition in the beverage industry, digital marketing strategies have become pivotal for enhancing sales and broadening consumer reach. The sale of soda beverages is increasingly competitive in the digital era, with more brands leveraging online platforms, necessitating the implementation of effective and relevant marketing strategies. One of the steps taken is conducting market analysis to gain a deeper understanding of consumer preferences and selecting suitable social media platforms such as Instagram and TikTok, which attract demographics aligned with the target audience.Social media marketing encompasses the creation of engaging and creative content, along with interactive promotions that directly involve consumers, fostering a deeper connection with the brand. The execution of this strategy has demonstrated significant improvements in brand awareness, user interaction, and social media follower counts. Moreover, this marketing approach not only captures the attention of new consumers but also reinforces the loyalty of existing customers.In addition to compelling content, leveraging consumer data to personalize their experiences has also proven effective. By analyzing consumer habits and behaviors, brands can deliver more targeted and relevant messages, thereby enhancing customer loyalty and satisfaction. In conclusion, integrated, innovative, and data-driven digital marketing has proven effective in boosting sales and cultivating stronger relationships with consumers. With the right strategy, FizzyFun can solidify its position in the increasingly competitive soda market and expand its product promotion efforts to ensure continuous sales growth. ABSTRAK Dalam menghadapi persaingan yang ketat di industri minuman, strategi pemasaran digital menjadi kunci untuk meningkatkan penjualan dan memperluas jangkauan konsumen. Penjualan minuman soda semakin kompetitif di era digital, dengan semakin banyaknya merek yang memanfaatkan platform online, sehingga diperlukan strategi pemasaran yang efektif dan relevan. Salah satu langkah yang diambil adalah melakukan analisis pasar untuk memahami preferensi konsumen secara lebih mendalam, serta memilih platform media sosial yang tepat seperti Instagram dan TikTok, yang memiliki pengguna dengan demografi yang sesuai. Pemasaran melalui media sosial mencakup pembuatan konten kreatif yang menarik dan promosi interaktif yang melibatkan konsumen secara langsung, sehingga akan merasa lebih terhubung dengan merek. Pelaksanaan strategi ini menunjukkan peningkatan yang signifikan dalam kesadaran merek, interaksi pengguna, serta jumlah pengikut di media sosial. Selain itu, pemasaran ini tidak hanya mampu menarik perhatian konsumen baru, tetapi juga memperkuat loyalitas pelanggan yang sudah ada. Tidak hanya melalui konten yang menarik, penggunaan data konsumen untuk menyesuaikan pengalaman mereka juga memberikan hasil yang baik. Dengan memanfaatkan analisis kebiasaan dan perilaku konsumen, merek dapat menyampaikan pesan yang lebih tepat sasaran dan relevan, sehingga meningkatkan loyalitas dan kepuasan pelanggan. Kesimpulannya, pemasaran digital yang terintegrasi, inovatif, dan berbasis data terbukti efektif dalam meningkatkan penjualan serta membangun hubungan yang lebih kuat dengan konsumen. Dengan strategi yang tepat, FizzyFun dapat memperkuat posisinya di pasar minuman soda yang semakin kompetitif, serta memasarkan produknya secara lebih luas agar penjualan terus meningkat.